Relationship between Communication Skills and Patient’s Aggressive Behavior among Nursing at Diwaniyah Teaching Hospital - Abdulhassan, Ammar Abdulhamza (NIU Journal of Social Sciences; Vol 12 No 2 (2026): NIU Journal of Social Sciences, Vol. 12 No. 2, June 2026, 2026)
Communication skills are essential for building effective relationships, whether in professional They enable individuals to exchange ideas, feelings, and information in a clear and respectful manner that leads to understanding and cooperation its human interaction so this study started with objectives:  To determine the level of communication skills among nurses at AL Diwaniyah Teaching Hospital, to determine the association between nurses ‘demographic data and nurses’ communication skill and to explore the relationship between nurses' communication abilities  and patient aggressive behavior and determination of the level of the patient aggressive behavior according to the nursing staff work place Methodology: A quantitative descriptive approach was used. Random sample of 291 nurses were chosen from those working morning and evening shifts at Al-Diwaniyah Teaching Hospital. A data was collected using questionnaire. An exploratory study was conducted among 30 nurses outside the sample between December 9 to December 10, 2025. The Cronbach's alpha coefficient was 0.72, and the questionnaire was subjected to validity confirmation by experts within a period of two weeks. Results: The study, conduct at Al-Diwaniyah Teaching Hospital from September 1st, 2025, to April 1st 2026, revealed that the level of communication skills was moderate. The results indicated evidence of a relationship between demographic variables and communication skills. The results indicated that 69.1% of participants had been exposed to aggressive behavior. The Person correlation coefficient between communication skills and exposure to aggressive behavior was (), indicating a very weak relationship between the two variables. Conclusion: The study results indicate a moderate relationship between communication skills and aggressive patient behavior (r = -.481**, p-value ≤ 0.01). It is recommended to enhance specialized training, create a favorable work environment, and study job stability indicators to ensure employee safety and improve service quality. Keywords:  Communication skills, aggressive behavior, nursing staff, workplace safety.